2019
DOI: 10.1002/jbm.b.34303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between poliglecaprone and chitosan absorbable sutures in laparorrhaphy and cecorrhaphy in rabbits

Abstract: Despite improvements in the development of sutures and surgical techniques of laparorrhaphy and enterorrhaphy, complications resulting from the process of intestinal and muscular healing after simple enterorrhaphy or enteroanastomoses followed by laparorrhaphy are still frequent. The poliglecaprone 25 (PG) suture is commonly used in this type of surgical procedure due to the induction of little tissue reaction, rapid absorption by hydrolysis, and the absence of capillarity. The chitosan (CG) yarn, despite prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[ 22,23 ] They observed that the PCL/CS blended scaffold was more favorable for cell culture with a better spreading of cultured cells than the pure PCL. [ 18,24,25 ] Prabhakaran et al. also reported the same results but for peripheral nerve regeneration.…”
Section: Introductionmentioning
confidence: 66%
“…[ 22,23 ] They observed that the PCL/CS blended scaffold was more favorable for cell culture with a better spreading of cultured cells than the pure PCL. [ 18,24,25 ] Prabhakaran et al. also reported the same results but for peripheral nerve regeneration.…”
Section: Introductionmentioning
confidence: 66%
“…These are non-irritants, non-immunogenic, non-hemolytic, histocompatible, and naturally degradable. These materials are widely used to manufacture artificial skin 45 , 46 , absorbable sutures 47 , 48 , and drug carriers 49 - 51 . Well-studied polysaccharide-based hemostatic materials include chitosan, cellulose, HA, and alginate.…”
Section: Introductionmentioning
confidence: 99%